Superdotados acompanhados em serviço especializado: características clínicas, sociodemográficas e qualidade de vida - Santos, Lara Cristina Antunes dos [UNESP] (2015)
The objective of this study is to characterize the profile concerning social demographic and clinic aspects, and to evaluate life quality of gifted students assisted by a specialized service. The social demographic characteristics, the gifted student intelligence tests performance, their previous diagnostics/comorbidities and the behavior/emotional problems were described to analyze the relations among these characteristics and their life quality. The gifted students with 18 years old or less were selected from child neurology outpatient clinic of Learning Deviations (Learning Deviations Ambulatory) of Clinical Hospital of UNESP- Botucatu in the years 2008 to 2014 by Wechsler intelligence scales results above 120. All of them were sent to the service for behavior and/or learning problems and had no suspect of being gifted before the evaluation. The following instruments were used: Wechsler intelligence scale, social demographic protocol elaborated for this study, the Brazilian version of Child Behavior Checklist (CBCL) and of life quality questionnaires: Pediatric Life quality questionnaire (PedsQLTM). The 10.0 STATA Program was used for statistical analysis. Descriptive analysis was made first, with checking of data consistency and corrections when needed. Prevalence estimative was associated of trust intervals of 95% and measures of central tendency and dispersion were calculated. The age median was 10 and the Intelligence Quotient mean 129,59. The Total Emotional/Behavior Problems and Internalization Scales were in the clinical range for respectively 51,8% and 66,7% of the gifted students. The Emotional Dimension of Life Quality showed the lower score for the gifted and their parents. Life Quality was inversely proportional to Executive Intelligence Quotient and Perceptual Organization and was also clinical range of Anxiety/Depression Syndrome from CBCL. The results suggest that life quality can be worse as specific abilities have ...